2009
DOI: 10.1097/aci.0b013e32832d5311
|View full text |Cite
|
Sign up to set email alerts
|

Basophil activation tests in the evaluation of immediate drug hypersensitivity

Abstract: BAT sensitivity in beta-lactam allergy was 50%, and specificity ranged from 89 to 97%. There are several studies to validate the BAT in allergy to muscle relaxants showing a sensitivity ranging from 54 to 64% with a specificity of 100 and 93%. The sensitivity of a test for evaluating immediate allergic reactions to drugs may decrease over time. To date, the BAT is the only in-vitro diagnostic method that has been validated for the diagnosis of both IgE-mediated and hypersensitivity reactions to NSAIDs. With re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 50 publications
3
42
0
2
Order By: Relevance
“…[13][14][15][16][17][18] Some researchers suggested that CD203c is more sensitive than CD63 for the diagnosis of drug allergy. 14,20) This may be due to the fact that CD63 is not only a marker of activated basophils but also of platelets and leukocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17][18] Some researchers suggested that CD203c is more sensitive than CD63 for the diagnosis of drug allergy. 14,20) This may be due to the fact that CD63 is not only a marker of activated basophils but also of platelets and leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry-based tests for peripheral blood basophils can easily quantify these in vitro reactions, which presumably represent their in vivo activity for hymenoptera, latex, food and drug allergies. [9][10][11][12][13] The sensitivity of the basophil activation test for the diagnosis of drug allergy has been reported; the reported sensitivities for the diagnosis of allergy to β-lactams, [14][15][16] quinolones 17) and rocuronium 18) are 33-67%, 71.1% and 80%, respectively. In addition, increased CD63 expression on basophils has been reported in a patient with cisplatin allergy.…”
mentioning
confidence: 99%
“…Several tests have been developed based on the capacity ofbasophils to be activated and release different mediators (12). The basophil activation test (BAT) is a useful tool in the in-vitro diagnosis of immediate hypersensitivity reactions to drugs, whether these are caused by IgE-dependent mechanisms or other mechanisms leading to the release of histamine and other mediators of immediate hypersensitivity reactions.…”
Section: Diagnosis Of Hypersensitivity To Antibioticsmentioning
confidence: 99%
“…results obtained in terms ofsensitivity and specificity with this technique are encouraging and allow a diagnosis to be made in a not negligible number of cases, thus avoiding the use of chalIenge tests. The combination of the results from BAT and immunoassay increaseds sensitivity to 65.7% or even to 85% when the results of skin tests were also included, without changing the-specificity (12).…”
Section: Diagnosis Of Hypersensitivity To Antibioticsmentioning
confidence: 99%
“…Numerous studies over recent years have shown the usefulness of this technique for the in vitro diagnosis of allergic diseases (Ebo et al, 2006a(Ebo et al, , 2004aKleine-Tebbe et al, 2006) involving different allergens, such as inhalants (Paris-Köhler et al, 2000;Saporta et al, 2001), hymenoptera venoms (Sabbah et al, 1998;Sainte-Laudy et al, 2000), or latex (Ebo et al, 2002;Sanz et al, 2003). For the diagnosis of allergy to drugs like muscle relaxants (Abuaf et al, 1999;Monneret et al, 2002), betalactam antibiotics (Sanz et al, 2001b(Sanz et al, , 2002aTorres et al, 2004), pyrazolones (Sabbah et al, 1997;Sanz et al, 2005) and non steroidal anti-inflammatory drugs (NSAIDs) BAT has opened up an important diagnostic pathway, either on its own or combined with other techniques (de Weck et al, 2008b;Gamboa et al, 2003a), allowing avoidance of challenge tests in an important number of cases (Hausmann et al, 2009;Sanz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%